2022
DOI: 10.3389/fonc.2022.873354
|View full text |Cite
|
Sign up to set email alerts
|

Breast Metastasis From Rectal Signet-Ring Cell Carcinoma: A Case Report and Review of Literature

Abstract: BackgroundMetastatic rectal cancer (mRC) of the breast is an extremely rare clinical situation. There are few reported cases in domestic or foreign literature. The clinicopathologic characteristics along with the diagnostic and therapeutic strategies of such cases remain relatively unclear. Here, we would like to provide our comprehensive insights into this rare entity.MethodsWe present a case that till now is the first reported breast metastasis from rectal cancer pathologically diagnosed as a signet-ring cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Compared to the liver or lung metastases, rectal cancer breast metastasis (RCBM), let alone vulvar metastasis, is rather uncommon in existing literature (17)(18)(19). Except 2 male patients, RCBM mainly involved the female in previous reports (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the liver or lung metastases, rectal cancer breast metastasis (RCBM), let alone vulvar metastasis, is rather uncommon in existing literature (17)(18)(19). Except 2 male patients, RCBM mainly involved the female in previous reports (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…RCBM presents at a younger age 47.7 years (17) than primary rectal cancer (63 years) (5). The mean interval between the initial diagnosis of rectal cancer and the occurrence of breast metastasis was reported to be 28.4 months (range, 5 months to 18 years) (17). Williams et al (25) suggested that breast metastasis usually served as a part of systemic metastases and was associated with poor expected survival, with a median survival of 10 months post diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Currently, only a small number of reports have described metastasis of malignant tumors, such as melanoma, lymphoma, and rectal cancer, to the breast. 7 Patients with breast metastasis usually have widespread disease and a poor prognosis. 4 Breast lump(s), pain, and nipple discharge are typical symptoms of primary breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Extramammary breast metastases are more common in patients with hematological and cutaneous melanoma [4]. However, the lung, ovary, cervix, prostate, kidney, gastrointestinal system, liver, and head and neck regions are other possible initial tumor sites [1,2,[4][5][6][7]. There were 73 cases of gastric cancer with breast metastasis published online up until June 2022, including 17 cases with breast and ovarian metastases and only 6 cases with bilateral breast and ovarian metastasis (Table 1).…”
Section: Introductionmentioning
confidence: 99%